STUDI KASUS BUDAYA POPULER FOMO TERHADAP MOTIF MAHASISWA UPR SEBAGAI AFFILIATOR DALAM PROGRAM TIKTOK AFFILIATE - Putri Diana Situmeang; Ida Bagus Suryanatha; Sontoe Sontoe (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2026)
This study examines the phenomenon of fear of missing out (FoMO) experienced by students at Palangka Raya University (UPR) when participating as affiliates in the TikTok Affiliate program, within the context of the development of the digital economy and the influence of popular culture. The background indicates that social media is increasingly evolving into a platform for conducting business through e-commerce and social commerce, influenced by digital popular culture and the FoMO mindset prevalent among students. The theories employed include Manuel Castells’ theory of the network society, which emphasizes the importance of digital connections, and Pierre Bourdieu’s theory of social practice, which focuses on the roles of habitus and social, cultural, and economic capital. This study aims to identify the reasons why students engage in the TikTok Affiliate program and how the fear of missing out (FoMO) influences their participation. The method used is qualitative with a case study approach, including interviews, observations, and document collection. The results show that FoMO encourages students to get involved due to the influence of friends, current trends, and economic factors. In conclusion, the fear of missing out (FoMO) and the use of digital networks influence how students behave economically today.